Gombrowicz in History and about History – a Revolt against the Form Entangled in Memory - Pieszak, Eryk (Sensus Historiae, 2023)
The article “Gombrowicz in History and about History” analyzes Gombrowicz’s selected works, on the one hand, as a personal historical source - the story of a specific person, and on the other hand, as a subjective message that fits into the entire work of the writer who tried to be a kind of philosopher describing contemporary times. Therefore, what is presented first is a certain ideal type of Gombrowicz’s approach to man and especially to history, which will be incorporated into postmodernist theory. Then, this concept is placed in the context of the event that was the creation and publication of the Kronos diary (many years after the author’s death) without, of course, ignoring the content of the work.